Enhanced index for water body delineation and area calculation using Google Earth Engine: a case study of the Manchar Lake. Issue 2 (24th November 2021) - Ismail, Muhammad Ali; Waqas, Maria; Ali, Amjad; Muzzamil, Mirza Muhammad; Abid, Uzair; Zia, Talha
Abstract: The sustainability of the hydrological and ecological ecosystems of any region requires continuous monitoring of the water bodies. Recent advancements in satellite-based remote optical sensors, big data analysis and cloud computing have given new dimensions to the field of water body studies including their detection as well as analysis. The present study extends the existing methods to assess the contemporary surface water detection and monitoring techniques via remote sensing. The proposed technique implies an improved hybrid approach for the purpose along with the calculation of the boundary areas. The study has been carried out on the Manchar Lake, the largest natural freshwater lake in Pakistan as well as in South Asia. The proposed hybrid water index along with the different existing water body detection indices and spectral bands have been worked out on the satellite images retrieved from the Google Earth Engine to detect and analyze the area/flow changes in the water body. Based on the 7 years of data, the proposed algorithm calculates the water body area more precisely. With limited availability of metadata about the study area, the results have been validated both qualitatively through national-met data and statistically. These results help to better preserve and improve the quality of the water resource. HIGHLIGHTS: The present work studies Manchar Lake, the largest water body located in the Sindh province of Pakistan. The present work proposes a new water index, WIBI, for delineation area calculation of the water bodies. This is the first limnological study to observe and display annual area variation trends for the lake. Study results can be used to better preserve and improve the quality of the water resources. Graphical Abstract